2020
DOI: 10.1053/j.gastro.2020.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of LIGHT by T Cells in Eosinophilic Esophagitis Promotes Differentiation of Esophageal Fibroblasts Toward an Inflammatory Phenotype

Abstract: BACKGROUND & AIMS: Eosinophilic esophagitis (EoE) is an antigen-mediated eosinophilic disease of the esophagus that involves fibroblast activation and progression to fibrostenosis. Cytokines produced by T-helper type 2 cells and transforming growth factor beta 1 (TGFb1) contribute to the development of EoE, but other cytokines involved in pathogenesis are unknown. We investigate the effects of tumor necrosis factor superfamily member 14 (TNFSF14, also called LIGHT) on fibroblasts in EoE. METHODS: We analyzed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 55 publications
(74 reference statements)
3
42
0
Order By: Relevance
“…T cells in EoE patients are also able to express the TNF-related cytokine LIGHT (TNF superfamily member 14), which can induce an inflammatory phenotype in fibroblasts ( Manresa et al, 2020 ).…”
Section: Focus On Type 2 Inflammation: the Protagonistsmentioning
confidence: 99%
“…T cells in EoE patients are also able to express the TNF-related cytokine LIGHT (TNF superfamily member 14), which can induce an inflammatory phenotype in fibroblasts ( Manresa et al, 2020 ).…”
Section: Focus On Type 2 Inflammation: the Protagonistsmentioning
confidence: 99%
“…We have previously reported that LIGHT up-regulates a distinct subset of genes with inflammatory properties in esophageal fibroblasts (Fig. 1a ) 17 . In addition to its ability to up-regulate inflammatory mediators, an analysis of the LIGHT-repressed transcriptome revealed that LIGHT down-regulates multiple mediators of homeostatic functions including WNT factors (WNT5A, WNT2B), WNT receptors and targets (FZD4 and OLFM2), bone morphogenetic proteins (BMP6) or type 3 semaphorins (SEMA3, Fig.…”
Section: Resultsmentioning
confidence: 87%
“…TGF-β1 enhances HVEM expression on esophageal fibroblasts, and cells pretreated with TGF-β1 and stimulated with LIGHT display enhanced expression of genes such as IL-32 or ICAM-1 17 corresponding to the requirement for HVEM for modulating these molecules shown above. To further assess the isolated importance of HVEM, we overexpressed HVEM (HVEM-OE) in the presence of LTβR silencing (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations